2019
DOI: 10.18203/issn.2455-4529.intjresdermatol20190052
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study of facial dermatoses

Abstract: <p class="abstract"><strong>Background:</strong> The attractiveness of the human body has always been an important issue in the fields of sociology, psychology, psychiatry and also in the field of dermatology. Because in most societies the face is usually a body part that is visible, imperfections of its skin is also visible, therefore its flawed appearance bears the potential to become a source of misery to some. The objective of the study was to study the various dermatological conditions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
1
1
Order By: Relevance
“…This is in accordance with the study by Bhagwat et al, who in their study on facial dermatoses found that 52% of patients were males. 6 A female preponderance (57.2%) was noted in a study by Henshaw et al, on teenage adolescents in Nigeria, in contrast to our study. 7 The male preponderance in our study maybe due to more chance for male teenagers to get medical help because of their mobility in our society than females.…”
Section: Discussioncontrasting
confidence: 93%
“…This is in accordance with the study by Bhagwat et al, who in their study on facial dermatoses found that 52% of patients were males. 6 A female preponderance (57.2%) was noted in a study by Henshaw et al, on teenage adolescents in Nigeria, in contrast to our study. 7 The male preponderance in our study maybe due to more chance for male teenagers to get medical help because of their mobility in our society than females.…”
Section: Discussioncontrasting
confidence: 93%
“…Secondary to the obligated and prolonged use of face mask during the COVID-19 pandemic, there has been an increase in the reported cases of facial dermatosis such as rosacea, acne, and seborrhoeic dermatitis [5][6][7]. Common inflammatory facial dermatosis is defined as skin lesions affecting the face, it is a group of dermatological conditions of the skin including "acne vulgaris (AV), papulopustular rosacea (PPR), erythematotelangiectatic rosacea (ETR), perioral dermatitis, seborrheic dermatitis (SD), and atopic dermatitis (AD) [8]. It has been suggested in previous studies that prolonged wearing of face mask increases friction, occlusion, and causes hyperhydration which leads to a breach in the epidermal integrity of the skin, thus causing the apparent damage which manifests as facial dermatosis [9].…”
Section: Introductionmentioning
confidence: 99%